Application of rhizobia boosts the growth and yield of faba bean (Vicia faba L.) under field condition - Bhomik, Indrojit Chandra; Rashid, Md Harun-Or; Paul, Newton Chandra; Yesmin, Most. Monira; Saha, Kallyan Kanty; Rashid, Md. Harun; Paul, Swapan Kumar (Fundamental and Applied Agriculture, 2022)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh from November 2019 to March 2020 to study the effect of rhizobium strains on the growth and yield of faba bean (Vicia faba L.). The experiment consisted of two local varieties of faba bean, viz. black seeded faba bean and brown seeded faba bean and five rhizobium strains, viz. FM-1a, Faba-2, Faba-10, Mix-1 (1a, 2, 10), Mix-2 (153, 129, 640), and urea, and control. The experiment was laid out in a randomized complete block design with three replications. Results revealed that rhizobia exerted a significant influence on the growth and yield of faba bean varieties. In case of variety, brown seeded faba bean produced the highest number of nodules plant−1 (69.90), nodule dry weight plant−1 (7.26 mg), dry weight plant−1 (166 g), number of pods plant−1 (41.08), number of seeds pod−1 (2.87), 100-seed weight (22.71 g), seed yield (2.21 t ha−1) and stover yield (3.28 t ha−1) than black seeded faba bean. On the other hand, the highest SPAD value (40.06), number of nodules plant−1 (75.50), nodule dry weight plant−1 (7.143 mg), pod length (4.38 cm), number of pods plant−1 (41.83) and seed yield (2.22 t ha−1) of faba bean were recorded from rhizobium strain FM-1a. Again, in case of interaction, the highest number of nodules plant−1 (85.67), nodule dry weight plant−1 (8.27 mg), dry weight plant−1 (198 g), number of pods plant−1 (47.33) and 100-seed weight (23.48 g) were recorded in brown seeded faba bean with rhizobial strain FM-1a. The highest seed yield (2.66 t ha−1) and stover yield (3.26 t ha−1) were recorded in brown seeded faba bean with rhizobial strain FM-1a. Based on this result it can be concluded that brown seeded faba bean with rhizobial strain FM-1a could be a promising combination for faba bean cultivation.